A heterometallic macrocycle as a redox-controlled molecular hinge. Issue 5 (18th December 2014) - Schouwey, Clément; Papmeyer, Marcus; Scopelliti, Rosario; Severin, Kay
Abstract : The geometry of a heterometallic Pt–Cu macrocycle is controlled by the redox state of the Cu centers. An elongated form with a long Pt⋯Pt distance is observed for Cu(i ), whereas a folded form with a short Pt⋯Pt distance is found for Cu(ii ). Abstract : The ability to modify the structure of nanoscopic assemblies in a controlled fashion is an important prerequisite for the creation of functional supramolecular systems. Here, we describe a heterometallic Pt2 Cu2 -macrocycle which behaves as a molecular hinge. A square-planar Pt(ii ) complex with pendent 2-formylpyridine groups was synthesized and structurally characterized. Condensation of the complex with benzylamine followed by reaction with Cu(MeCN)4 BF4 resulted in the formation of a rectangular Pt2 Cu2 -macrocycle. Upon chemical oxidation of the Cu centers, the macrocycle folds up to adopt a butterfly-like geometry in which the Pt centers approach each other. This process can be reversed by chemical reduction.